TV journalism and power in presidential elections - Porcello, Flávio A. C. (Brazilian journalism research, 2009)
During the early years of television´s existence, when the luminous screen glowing in the middle of the living room was considered to be only a household appliance, there were some people who said that “TV is to watch, not to study” (!). And thus, due mainly to this bias, the academic world showed resistance to the first theoretical works and field research on this media which, among the conventional communication media, is without the slightest doubt the most influential form of political persuasion and disseminator of models and social practices. If at some time someone thought that TV´s influence on society did not deserve profound studies, today this serious error of evaluation is seen as responsible for the delay in the initiation of a serious study devoted to revealing the true facts. TV influences the entire political process, and how!